Research Design. Qualitative, quantitative and mixed methods approaches (Revista Peruana de Investigación Educativa, 2015)
Creswell, J.W. (2014).Research Design. Qualitative, quantitative and mixed methods approaches(4a ed.). Thousands Oaks, CA: Sage.